2017
DOI: 10.1186/s40991-017-0021-0
|View full text |Cite
|
Sign up to set email alerts
|

GOOGLE: a reflection of culture, leader, and management

Abstract: This paper provides a viewpoint of the culture and subcultures at Google Inc., which is a famous global company, and has a huge engineering staff and many talented leaders. Through its history of development, it has had positive impacts on society; however; there have been management challenges. The Board of Directors (BoDs) developed and implemented a way to measure the abilities of their managers, which helped to identify problems. This paper will analyze the case study of Harvard Business Review, Oxygen Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
0
28
0
2
Order By: Relevance
“…This finding is also in line with previous studies which revealed that employee engagement allows employees to accomplish more than what is needed for them. Engaged employees have the ability to create great value for an organization by generating high valued outcomes in their course of work (Tran, 2017). Employee engagement can allow employees to be more proactive and creative thinkers, leading toward low turnover intentions and reduced absenteeism.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…This finding is also in line with previous studies which revealed that employee engagement allows employees to accomplish more than what is needed for them. Engaged employees have the ability to create great value for an organization by generating high valued outcomes in their course of work (Tran, 2017). Employee engagement can allow employees to be more proactive and creative thinkers, leading toward low turnover intentions and reduced absenteeism.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Additionally, 30% of employee time is allocated to learning and development, highlighting the importance of time for individual reflection and self-development of cognitive abilities. Ethics is addressed through specific customized training sessions focused on issues typically encountered in particular situations or projects (Tran 2017).…”
Section: Teamworkmentioning
confidence: 99%
“…This study sought to address this gap by examining how post-merger restructuring influences organizational development of banks. As Tan (2017) explain, mergers bring together organizations that had distinct internal and external resources, customers, culture, and process (Tran, 2017). Therefore, the merger process is not only a financial transaction but also an institutional wide occurrence that require a lot restructuring and reorganization.…”
Section: Introductionmentioning
confidence: 99%